THE ASSOCIATION BETWEEN VISUAL PERFORMANCE WITH ABERRATION USING QUALITY OF LIFE OF REFRACTIVE CORRECTION (QIRC) QUESTIONNAIRE IN MODERATE AND HIGH MYOPIC PATIENTS - Rosley, Nursyahidatul Fasha; Hilmi, Mohd Radzi; Md-Muziman-Syah, Md Mustafa (International Journal of Allied Health Sciences, 2021)
Aims: This study was done to find out the association between visual performance with aberration using quality of life impact of refractive correction (QIRC) questionnaire in moderate and high myopic groups. Methodology: 21 participants were recruited with age ranging from 19 to 25 years old for both male and female having spherical refractive error between -3.00D to -5.00D (moderate myopia) or more than -5.00D (high myopia) and maximum cylindrical error of -1.25DC. This study was conducted in International Islamic University Malaysia (IIUM) Eye Specialist Clinic (IESC), Kulliyyah of Medicine, Kuantan, Pahang, Malaysia and IIUM Optometry Clinic (IMC), Kulliyyah of Allied Health Sciences on 21 subjects ranging from moderate and high myopia using WASCA analyzer. Results: Results show that there is a positive relationship between moderate and high myopia to third- and fourth-order aberration (p<0.05) while QIRC mean scores of high myopia yield a lower mean value to total HOA as compare to moderate myopic group, indicating lower satisfaction on their visual performance. However, there is a weak correlation found between QIRC results and aberration (p>0.05). Conclusion: This study found that there is a weak relationship between different degrees of myopia and aberration with QIRC questionnaire. Keywords: aberration, refractive error, myopia, QIRC, quality of life